2011
DOI: 10.1093/nar/gkr181
|View full text |Cite
|
Sign up to set email alerts
|

A novel DNA nuclease is stimulated by association with the GINS complex

Abstract: Chromosomal DNA replication requires the spatial and temporal coordination of the activities of several complexes that constitute the replisome. A previously uncharacterized protein, encoded by TK1252 in the archaeon Thermococcus kodakaraensis, was shown to stably interact with the archaeal GINS complex in vivo, a central component of the archaeal replisome. Here, we document that this protein (TK1252p) is a processive, single-strand DNA-specific exonuclease that degrades DNA in the 5′ → 3′ direction. TK1252p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
92
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(105 citation statements)
references
References 34 publications
11
92
2
Order By: Relevance
“…Pol D also interacts strongly with PCNA, conferring the ability to extend rapidly along long stretches of template DNA (28-30). These properties and fast, accurate, and processive DNA synthesis together with evidence that Pol D assembles in vivo into complexes that contain other replisome components (13,31,32) provide consistent support for the hypothesis that Pol D may replicate archaeal genomic DNA.To test this hypothesis, we took advantage of the genetic technologies now available for Thermococcus kodakarensis (33) to manipulate the in vivo structure and expression of Pol B (encoded by TK0001 [34]) (Fig. 2) and Pol D (encoded by TK1902 [DP1] and TK1903 [DP2]).…”
mentioning
confidence: 87%
“…Pol D also interacts strongly with PCNA, conferring the ability to extend rapidly along long stretches of template DNA (28-30). These properties and fast, accurate, and processive DNA synthesis together with evidence that Pol D assembles in vivo into complexes that contain other replisome components (13,31,32) provide consistent support for the hypothesis that Pol D may replicate archaeal genomic DNA.To test this hypothesis, we took advantage of the genetic technologies now available for Thermococcus kodakarensis (33) to manipulate the in vivo structure and expression of Pol B (encoded by TK0001 [34]) (Fig. 2) and Pol D (encoded by TK1902 [DP1] and TK1903 [DP2]).…”
mentioning
confidence: 87%
“…Archaea possess a simple homohexameric MCM (5, 7). In addition, archaeal homologs of GINS and Cdc45 have been identified (8)(9)(10)(11)(12)(13)(14). In species of the genus Sulfolobus, we have previously demonstrated that the GINS complex interacts with the N-terminal domains of MCM (8).…”
mentioning
confidence: 99%
“…One of them interacts with Hef (in this study) and the other interacts with GINS, an essential factor for DNA replication initiation and elongation in Eukarya and Archaea, which may be a component of the replicative helicase complex. The latter RecJ-like protein was reported as the GINS-associated nuclease (GAN), and may be involved in lagging strand processing (52). Furthermore, characterization of the GAN ortholog from P. furiosus revealed the 3Ј-5Ј exoribonuclease activity, which may function in proofreading for primer synthesis (53).…”
Section: Discussionmentioning
confidence: 99%